PEMBERIAN KOMBINASI MASASE TEKNIK PETRISSAGE (KNEADING) DAN PISANG AMBON (MUSA PARADISIACA) TERHADAP EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Antri Ariani; Dewi Nurlaela Sari; Agung Agung Sutriyawan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
The purpose of this study was to determine the effect of giving a combination of petrissage (Kneading) and Ambon banana (Musa Paradisiaca) massage techniques to Emesis Gravidarum in first trimester pregnant women in Kencana Village, Rancaekek Health Center.The research method uses a quasi-experimental approach with a one group pre-post test design approach. The pre-test and post-test measurements were carried out using a valid and reliable PUQE (Pregnancy Unique Quantification of Emesis) instrument so that researchers did not need to test the validity and reliability to measure the scale of nausea and vomiting.The results showed that the statistical test value was known to be p-value 0.000 or p-value <0.05, which means that there is an effect of giving a combination of petrissage (kneading) and banana (Musa paradisiaca) massage techniques to emesis gravidarum in first trimester pregnant women in Kencana Village, Region Rancaekek Health Center in 2021.Suggestion Giving a combination of petrissage technique massage (kneading) and Ambon banana (Musa paradisiaca) can be given to pregnant women in the first trimester to reduce emesis gravidarum..